ANALISIS TINGKAT KERUSAKAN JALAN PADA JALAN RAYA BYPASS KRIAN KABUPATEN SIDOARJO DENGAN METODE PAVEMENT CONDITION INDEX (PCI) - Paulinus Alan Tangke; Harry Moetriono (LPPM Universitas Abdurrab, 2023)
Roads are a land transportation sector that is often used by Indonesian citizens to travel far or near. Because the development of globalization also affects the level of mobility which has an impact on the increasing use of vehicles, resulting in the volume load of vehicles exceeding the planned road class limits, so that the quality and age of pavement will decrease. The location of this research was conducted to analyze pavement damage to road conditions on damage to the Jl. Krian bypass with a length of 3 km. The method used for this research is PCI (Pavement Condition Index) with the aim of finding values based on the type, level and extent of damage to the method used to determine the risk of damage and risk response to the roads being surveyed. The results of the research on the Jl. Bypass Krian STA 0+000 – 3+000 based on the PCI method gets a total value of 47.6% Moderate (Fair) with the highest percentage PCI value of road conditions being 38.50% in Moderate road conditions (Fair), 21.50% on Good road conditions, 20% on Poor road conditions, 16.60% on Very Good road conditions and 3.30% on Very Poor road conditions with reference to the PCI section matrix the road needs to be repaired.